1996
DOI: 10.1016/s0886-3350(96)80114-3
|View full text |Cite
|
Sign up to set email alerts
|

Three year results of refractive keratotomy using the Casebeer System

Abstract: Using the Casebeer system for refractive keratotomy, we obtained 20/40 or better uncorrected visual acuity in 96% of eyes with low to moderate levels of myopia. However, a significant number of enhancement procedures, 36% overall, were required to achieve this level of success. Hyperopic shift remains a significant concern following radial keratotomy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 36 RK yields acceptable refractive results with 60% of patients within 1 diopter of the intended result. 35 , 37 On the other hand, RK can lead to a progressive overcorrection and resulting hypermetropia. As a result of this shortcoming and with the rise of modern laser-based refractive procedures, RK has been used less frequently from the mid-1990s onwards.…”
Section: Iol Power Calculation After Rkmentioning
confidence: 99%
“… 36 RK yields acceptable refractive results with 60% of patients within 1 diopter of the intended result. 35 , 37 On the other hand, RK can lead to a progressive overcorrection and resulting hypermetropia. As a result of this shortcoming and with the rise of modern laser-based refractive procedures, RK has been used less frequently from the mid-1990s onwards.…”
Section: Iol Power Calculation After Rkmentioning
confidence: 99%
“…The procedure works reasonably well for low degrees of myopia. A prospective study of the procedure set up in the 1980s and followed for 10 years showed 60% of patients were within 1 dioptre of the intended result, and that uncorrected visual acuity was 20/20 in 53% of patients, and 85% of patients had 20/40 or better2; a more recent study with modified techniques showed some improvement in results 32 and since the advent of excimer laser treatment, radial keratotomy is used less frequently.…”
Section: Correction Of Myopiamentioning
confidence: 99%